1987
DOI: 10.1109/t-uffc.1987.26936
|View full text |Cite
|
Sign up to set email alerts
|

Range Finding and Surface Characterization Using High-Frequency Air Transducers

Abstract: The design and applications of high-frequency piezoelectric air transducers are described. Two types of thickness mode air transducers are designed and fabricated using newly synthesized acoustic matching layers with an acoustic impedance as low as 0.3 Mrayls. The insertion losses of these transducers are improved by 32-45 dB compared to that of the transducer without a matching layer. Use of a l-MHz double matching layer transducer with a good RF pulse response for range finding has revealed that the measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 3 publications
0
21
0
5
Order By: Relevance
“…It is generally understood that increasing ultrasound frequency improves detection resolution (Coleman et al, 2004;Yano, Tone & Fukumoto, 1987) and reduces dead zone length (Bruinsma et al, 2006). However, the high attenuation in air which increases with frequency is a great challenge (Magori, 1994;Yano, Tone & Fukumoto, 1987).…”
Section: Ultrasonic Sensing (Us)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally understood that increasing ultrasound frequency improves detection resolution (Coleman et al, 2004;Yano, Tone & Fukumoto, 1987) and reduces dead zone length (Bruinsma et al, 2006). However, the high attenuation in air which increases with frequency is a great challenge (Magori, 1994;Yano, Tone & Fukumoto, 1987).…”
Section: Ultrasonic Sensing (Us)mentioning
confidence: 99%
“…However, the high attenuation in air which increases with frequency is a great challenge (Magori, 1994;Yano, Tone & Fukumoto, 1987). It is reported that 1 MHz signal can theoretically measure distance up to 20 cm (Yano, Tone & Fukumoto, 1987), while 2 MHz signal can measure up to few centimeters (Noble et al, 1995). Recently, very high frequency ultrasonic transducers are reported for various high resolution biomedical applications.…”
Section: Ultrasonic Sensing (Us)mentioning
confidence: 99%
“…La resonancia (cuarto de onda) de la capa de adaptación está perfectamente sintonizada con la frecuencia del transductor. La mejor sensibilidad se obtiene para una impedancia de la capa de adaptación ente 0.025 y 0.1×10 6 Kg/m 2 s sin presentar cambios muy acusados dentro de ese amplio margen de variación. No obstante, los resultados obtenidos para una capa de adaptación de impedancia 0.2×10 6 Kg/m 2 s son también muy positivos.…”
Section: Impedancia Acústica Específicaunclassified
“…Para el aire, la impedancia acústica específica toma un valor en torno a 410 Kg/m 2 s, mientras que para una cerámica piezoeléctrica tenemos valores en torno a 30×10 6 Kg/m 2 s. Esta fuerte desadaptación de impedancias entre el aire y cualquier cerámica piezoeléctrica tiene dos efectos negativos sobre el transductor cuando se intenta operar en aire (emitir o recibir señales ultrasónicas al aire o desde el aire respectivamente):…”
Section: Introductionunclassified
“…An alternative to the laser techniques is to develop ultrasonic transducers which will operate satisfactorily with air coupling. Although recent improvements in ultrasonic technology have demonstrated the feasibility of airborne ultrasonic propagation in the low MHz frequency range [5], few attempts have been made to monitor other than surface reflection data. There have been demonstrations of relatively crude, dual transducer, through transmission airborne systems [6], but the results reveal insufficient sensitivity for successful operation in practical environments.…”
Section: Introductionmentioning
confidence: 99%